2009
DOI: 10.1897/ieam_2008-080.1
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls and hudson river white perch: implications for population‐level ecological risk assessment and risk management

Abstract: Risk assessments and risk management decisions concerning risks to wild fish populations resulting from exposures to polychlorinated biphenyls (PCBs) and related chemicals have been based primarily on observations of effects of chemicals on individual organisms. Although the development and application of population-level ecological risk-assessment methods is proceeding at a rapid pace, the organism-level approach is still being justified by arguments that population-level ecological risk assessment is in an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 34 publications
1
25
1
1
Order By: Relevance
“…We have applied several of these in this assessment. Predicted effects on productivity based on concentrations of PCDD/DF-TEQs WHO-Avian in eggs and nestlings, or in the diet, were compared with nesting success observed for TS in a site-specific multiple lines of evidence assessment of hazard [50,64,[77][78][79]. Sampling a single egg per nest was selected for this assessment, based on previous studies [38,80,81] that indicated that laying order does not affect concentrations, and that exposure is better estimated than from extrapolation from abiotic matrices and can be accounted for in subsequent nesting success calculations.…”
Section: Multiple Lines Of Evidence and Population-level Effectsmentioning
confidence: 99%
“…We have applied several of these in this assessment. Predicted effects on productivity based on concentrations of PCDD/DF-TEQs WHO-Avian in eggs and nestlings, or in the diet, were compared with nesting success observed for TS in a site-specific multiple lines of evidence assessment of hazard [50,64,[77][78][79]. Sampling a single egg per nest was selected for this assessment, based on previous studies [38,80,81] that indicated that laying order does not affect concentrations, and that exposure is better estimated than from extrapolation from abiotic matrices and can be accounted for in subsequent nesting success calculations.…”
Section: Multiple Lines Of Evidence and Population-level Effectsmentioning
confidence: 99%
“…Furthermore, the promotion of long-term studies on natural history and demographics of new species would enhance the ability to investigate AOPs across diverse species. This would, in turn, enable the application of the methodology presented in the present study (of using a biomarker or in situ effects-based measurement in a given local or sentinel species of fish to evaluate toxicity) to be extrapolated at a population scale using population models developed for other species [5,6,[8][9][10]12,58].…”
Section: Discussionmentioning
confidence: 99%
“…The application of models offers an effective methodology for addressing the toxicity of an increasing number of chemicals and chemical mixtures for risk assessment [3,4,8]. Furthermore, population modeling, in combination with field-based monitoring assessments, may provide the ability to predict population dynamics over time and across sites in response to remedial actions [5,7,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…PCBs declined an order of magnitude since the 1970s in adult striped bass (Morone saxatilis) and white perch (Morone americana) in the lower Hudson River (Albany to New York, New York, USA) and during this time, reproductive success was not related to temporal trends in PCBs (Barnthouse et al, 2003(Barnthouse et al, , 2009. In fact, a positive correlation between maternal lipid-based PCBs in white perch and subsequent abundance at age-1 was observed (Barnthouse et al, 2009). In these studies and a more current study (Maceina and Sammons, 2013), PCBs were about an order of magnitude lower than those measured in fish from the upper Hudson River in the early-mid 1990s.…”
Section: Discussionmentioning
confidence: 99%